2011
DOI: 10.1021/jp201251j
|View full text |Cite
|
Sign up to set email alerts
|

Energetics and Interactions of Mixed Halogen Adsorbates on the Si(100) Surface

Abstract: The energetics of various ordered structures of the Si(100) surface with a 1:1 mixture of two adsorbates (hydrogen–halogen) or (two halogens) are investigated using ab initio density functional theory (DFT) calculations. Through an analysis of the calculated energies of various ordered adsorbate structures, the nearest-neighbor and next-nearest-neighbor interactions between halogen adsorbates are unveiled and observed to fit well with a proposed electron-cloud overlap model. Systematic trends are revealed: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 35 publications
1
21
1
Order By: Relevance
“…Earlier experiments of HCl and HBr on Si(100) were performedin contrast to the present workat saturation coverage or on a hydrogenated surface . While dissociative attachment was found to be a major pathway, previous authors found evidence of the abstraction of single atoms, H or Cl, by the surface.…”
Section: Introductioncontrasting
confidence: 56%
“…Earlier experiments of HCl and HBr on Si(100) were performedin contrast to the present workat saturation coverage or on a hydrogenated surface . While dissociative attachment was found to be a major pathway, previous authors found evidence of the abstraction of single atoms, H or Cl, by the surface.…”
Section: Introductioncontrasting
confidence: 56%
“…The bond energy for I 2 , 1.48 eV, is smaller than that of Si−I, 2.34 eV. 5,28 From an energy point of view, the abstract adsorption is exothermic…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…If the mixed adsorbates form ordered structures, the basic building blocks for the Si(100):AH surface are either mixed occupation dimers (MOD) A-Si-Si-H (AH for short) or H-Si-Si-A (HA), or paired occupation dimers (POD) A-Si-Si-A (AA) or H-Si-Si-H (HH). Following a previous report [15], eight different ordered adsorbate structures can be formed as listed in Table 1 in a (4 × 2) cell. Labels "m" and "p" in Table 1 indicate that the structure is formed, respectively, by MODs and PODs.…”
Section: Interaction Model and Energy Calculationsmentioning
confidence: 99%
“…Particularly, the energy for (2 × 1)-p, E 8, AH , is the mean of the two energies for A-and H-terminated (2 × 1) structure, respectively. Because the interactions between H and A are presumably negligible [15], we can further reduce the number of terms in the interactions by assuming π HH = π AH = 0, where π = η, α, β, ρ, or γ. With these simplifications, the relative interaction energies E i for the mixed hydrogen-organic moiety terminated surfaces Si(100): AH contain only the interactions between two adsorbates A as listed in Table 1.…”
Section: Calculated Adsorbate-adsorbate Energy In Various Directionsmentioning
confidence: 99%
See 1 more Smart Citation